The young Oxford book of archaeology - Moloney, N. (Norah) (Oxford Oxford University Press, 1997)
Defines archaeology, examines how archaeologists work, surveys excavation methods, and visits archaeology sites--from Olduvai Gorge in Tanzania to the Garbage Project in America.
Keywords: Archaeology -- Juvenile literature; Antiquities -- Juvenile literature; Archaeology; Antiquities